Ancient histories of medicine : essays in medical doxography and historiography in classical antiquity - Eijk, Ph. J. van der (Studies in Ancient Medicine, 1999)
This collection of essays focuses on the ways in which Greek and Latin authors viewed and wrote about the history of medicine in the ancient world. Special attention is given to medical doxography, id est the description of the characteristic doctrines of the great medical authorities of the past. The volume examines the various attitudes to the history of medicine adopted by a wide range of ancient writers (e.g. Aristotle, Galen, Celsus, Herophilus, Soranus, Oribasius, Caelius Aurelianus). It discusses the historical sense of ancient medicine, the variety of versions of the medical past that were created and the wide range of purposes and strategies which medico-historical writing served. It also deals with the question of the sources, the role of historiographical traditions and the variety of literary genres of ancient medico-historical writing.